Transfusion associated graft versus host disease following whole blood transfusion: an unusual case of expanded dengue syndrome - Misra, Krushna Chandra; Kumar, Garipalli Srinivas Nikilesh; Munta, Kartik; Hariprasad, A.; D., Shiva Kumar G. (International Journal of Advances in Medicine, 2025)
Dengue infection presents in a diverse array of manifestations, including dengue fever (DF), dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). To include cases that do not fit the criteria for either DHF or DSS and show atypical manifestations across multiple organ systems, world health organization (WHO) coined the term expanded dengue syndrome (EDS). A 47-yr-old female presented with fever, chills, blanchable rash, itching and burning sensation all over body with skin peeling over the last 5 days. In the outside hospital, she developed melena and thrombocytopenia, for which she received 1unit packed red blood cells, 1 unit of single donor platelets from her brother. After 1 week she developed above symptoms and was referred to us for pancytopenia. On evaluation her platelets, leucocyte count was low with normal Hb levels. The bone marrow biopsy revealed a hypoplastic marrow accompanied by significant proliferation of pre-progenitor megakaryocytes. She had mild transaminitis, without hyperbilirubinemias. Blood culture grew candida spp, Enterococcus faecium. She received appropriate antibiotics along G-CSF. Skin biopsy revealed basal vacuolation, spongiosis in epidermis, necrotic epidermis, apoptotic keratinocytes scattered in intact epidermis suggestive of acute GVHD Gr-Ⅲ. Consequently, she was commenced on pulsed steroid regimen followed by maintenance dose. Within a week, her clinical condition improved and was discharged on tapering dose of steroids. The existence of donor-derived cells or DNA in the recipient’s blood or afflicted tissues must be documented to make conclusive diagnosis of TA-GVHD.